A new species of Theretra Hübner (Lepidoptera: Sphingidae) from the southern Western Ghats, India - Sondhi, Yash; Kitching, Ian J.; Basu, Dipendra Nath; Kunte, Krushnamegh (Zootaxa, 2017)
A new species of the genus Theretra Hübner [1819], Theretra shendurneensis sp. nov., is described from Shendurney Wildlife Sanctuary, southern Western Ghats, India, based on external and internal morphology, and genetic markers. The new species is compared in external and male genital morphology, genetic divergence and geographic range with three similar and closely related species: T. boisduvalii (Bugnion, 1839), T. sumatrensis (Joicey and Kaye, 1917) and T. rhesus (Boisduval, [1875]). Recent changes to the classification of Theretra are discussed and rejected.